A Re‐evaluation of Electron‐Transfer Mechanisms in Microbial Electrochemistry: Shewanella Releases Iron that Mediates Extracellular Electron Transfer. Issue 5 (19th February 2016) - Oram, Joseph; Jeuken, Lars J. C.
Abstract: Exoelectrogenic bacteria can couple their metabolism to extracellular electron acceptors, including macroscopic electrodes, and this has applications in energy production, bioremediation and biosensing. Optimisation of these technologies relies on a detailed molecular understanding of extracellular electron‐transfer (EET) mechanisms, and Shewanella oneidensis MR‐1 (MR‐1) has become a model organism for such fundamental studies. Here, cyclic voltammetry was used to determine the relationship between the surface chemistry of electrodes (modified gold, ITO and carbon electrodes) and the EET mechanism. On ultra‐smooth gold electrodes modified with self‐assembled monolayers containing carboxylic‐acid‐terminated thiols, an EET pathway dominates with an oxidative catalytic onset at 0.1 V versus SHE. Addition of iron(II)chloride enhances the catalytic current, whereas the siderophore deferoxamine abolishes this signal, leading us to conclude that this pathway proceeds via an iron mediated electron transfer mechanism. The same EET pathway is observed at other electrodes, but the onset potential is dependent on the electrolyte composition and electrode surface chemistry. EET pathways with onset potentials above −0.1 V versus SHE have previously been ascribed to direct electron‐transfer (DET) mechanisms through the surface exposed decaheme cytochromes (MtrC/OmcA) of MR‐1. In light of the results reported here, we propose that the previously identified DET mechanism of MR‐1 needs to be re‐evaluated. Abstract : How does S. oneidensis MR‐1 respire on electrodes? The extracellular electron‐transfer mechanism of S. oneidensis MR‐1 is studied with microbial electrochemistry by controlling the surface chemistry of the electrode. Electrochemical behaviour that has previously been ascribed to a direct electron‐transfer mechanism is brought into question by strong evidence that indicates iron redox cycling is responsible for anodic currents with onsets at 0.1 V versus SHE.